Association between the time to surgery and survival among patients with colon cancer: A population-based study. Issue 8 (August 2017) - Flemming, J.A.; Nanji, S.; Wei, X.; Webber, C.; Groome, P.; Booth, C.M.
Abstract: Factors associated with time-to-surgery (TTS) and survival in colon cancer has not been well studied. Cancer Care Ontario recommends surgery within 42 days of diagnosis and that 90% of patients meet this benchmark. We describe factors associated with TTS and survival in routine clinical practice. Methods: Retrospective population-based cohort study of patients receiving elective colonic resection after diagnosis of colon cancer in Ontario, Canada from 2002 to 2008 followed until 2012. Factors associated with TTS were identified using multivariate log-binomial and Quantile regression at 42 days and 90th percentiles. The association between TTS and cancer-specific (CSS) and overall survival (OS) were examined using multivariate Cox regression. Results: 4326 patients; median age 71 years and 52% male. Median TTS was 24 days (IQR 14–37); at the 90th percentile 56 days. Factors associated with TTS ≥ 42 days and >90th percentile included older age, co-morbid illness, surgeon volume, and stage I disease (P < 0.05 for all). In patients whose TTS was either at 42 days or 90th percentile, those ≥80 years old waited two weeks longer than those <60 years, individuals with co-morbid illness waited 10 days longer than without co-morbidity, and patients with stage I disease waited 10 days longer than those with stage IV disease (P < 0.05 for all). Delay in TTS > 42 days or >90th percentile was not associated with OS or CSS. Conclusion: Age, co-morbidity, and stage of cancer are associated with TTS. There was no association between TTS and CSS or OS.